The Antifungal Peptide MCh-AMP1 Derived From Matricaria chamomilla Inhibits Candida albicans Growth via Inducing ROS Generation and Altering Fungal Cell Membrane Permeability - Seyedjavadi, Sima Sadat; Khani, Soghra; Eslamifar, Ali; Ajdary, Soheila; Goudarzi, Mehdi; Halabian, Raheleh; Akbari, Reza; Zare-Zardini, Hadi; Imani Fooladi, Abbas Ali; Amani, Jafar; Razzaghi-Abyaneh, Mehdi (Frontiers in Microbiology, 2020)
The rise of antifungal drug resistance in Candida species responsible for life threatening candidiasis is considered as an increasing challenge for the public health. MCh-AMP1 has previously been reported as a natural peptide from Matricaria chamomilla L. flowers with broad-spectrum antifungal activity against human pathogenic moulds and yeasts. In the current study, the mode of action of synthetic MCh-AMP1 was investigated against Candida albicans, the major etiologic agent of life-threatening nosocomial candidiasis at cellular and molecular levels. Candida albicans ATCC 10231 was cultured in presence of various concentrations of MCh-AMP1 (16 to 64 µg/mL) and its mode of action was investigated using plasma membrane permeabilization assays, reactive oxygen species (ROS) induction, potassium ion leakage and ultrastructural analyses by electron microscopy. MCh-AMP1 showed fungicidal activity against Candida albicans at the concentrations of 32 and 64 µg/mL. The peptide increased fungal cell membrane permeability as evidenced by elevating of PI uptake and induced potassium leakage from the yeast cells. ROS production was induced by the peptide inside the fungal cells to a maximum of 64.8% at the concentration of 64 µg/mL. Scanning electron microscopy observations showed cell deformation as shrinkage and folding of treated yeast cells of Candida albicans. Transmission electron microscopy showed detachment of plasma membrane from the cell wall, cell depletion and massive destruction of intracellular organelles and cell membrane of the fungal cells. Our results demonstrated that MCh-AMP1 caused Candida albicans cell death via increasing cell membrane permeability and inducing ROS production. Therefore, MCh-AMP1 could be considered as a promising therapeutic agent to combat Candida albicans infections.